The Relationship Between Diet and Physical Activity Patterns and the Incidence of Overweight in Adolescents at SMK Minhajut Thulab Al Amin - Yana, Selvi; Princess Rahmah Alamsyah; Abdullah; Lara Ayu Lestari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Excessive body weight can cause digestive disorders, fatigue, limited mobility, psychological distress, joint pain or inflammation especially in the knees . In addition, being overweight can also increase the risk of degenerative diseases, which can reduce productivity, endanger the economy, and increase pain levels. Objective : to identify dietary patterns and low physical activity, which contribute to the incidence of overweight in adolescents at SMK Minhajut Thulab Al Amin in Mesuji Regency. Method: Quantitative research with a cross-sectional approach . The study sample was 127 students with a random sampling technique . Data analysis used univariate and bivariate with the chi-square test. Results : That dietary patterns and physical activity independently and synergistically increase the risk of overweight . The combination of the two provides a stronger effect than each factor separately. Conclusion: There is a relationship between diet ( p-value 0.01) and physical activity ( p-value 0.001) with the incidence of overweight in adolescents in SMK Minhajut Thulab Al Amin. It is expected that adolescents will do physical activities more routinely and the importance of integrated interventions to overcome the problem of overweight, namely by improving diet and increasing physical activity simultaneously